2003
DOI: 10.1038/sj.jea.7500289
|View full text |Cite
|
Sign up to set email alerts
|

Influence of traffic patterns on particulate matter and polycyclic aromatic hydrocarbon concentrations in Roxbury, Massachusetts

Abstract: Vehicle emissions have been associated with adverse health effects in multiple epidemiological studies, but the sources or constituents responsible have not been established. Characterization of vehicle-related exposures requires detailed information on spatial and temporal trends of various pollutants and the ability to predict exposures in unmonitored settings. To address these issues, in the summer of 2001 we measured continuously particle-bound polycyclic aromatic hydrocarbons (PAHs), ultrafine particles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 28 publications
5
39
0
Order By: Relevance
“…However, we were unable to identify other studies exploring the effects of ambient temperature and wind speed on UFP exposures in transportation environments. Nevertheless, previous studies have observed inverse relationships between wind speed and roadside UFP levels (Zhu et al, 2002(Zhu et al, , 2006aLevy et al, 2003) as well as between temperature and ambient UFP counts (Jeong et al, 2004(Jeong et al, , 2006 and therefore our results appear to be consistent with previous findings. Indeed, lower UFP exposures were expected at increased wind speeds owing to the dispersion of vehicular emissions, and the observed inverse correlation between ambient temperature and UFP exposures was not surprising as the formation of UFPs from traffic exhaust depends in part on vapor condensation (Korhonen et al, 2004;Kulmala et al, 2004) which is favored at lower temperatures.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, we were unable to identify other studies exploring the effects of ambient temperature and wind speed on UFP exposures in transportation environments. Nevertheless, previous studies have observed inverse relationships between wind speed and roadside UFP levels (Zhu et al, 2002(Zhu et al, , 2006aLevy et al, 2003) as well as between temperature and ambient UFP counts (Jeong et al, 2004(Jeong et al, , 2006 and therefore our results appear to be consistent with previous findings. Indeed, lower UFP exposures were expected at increased wind speeds owing to the dispersion of vehicular emissions, and the observed inverse correlation between ambient temperature and UFP exposures was not surprising as the formation of UFPs from traffic exhaust depends in part on vapor condensation (Korhonen et al, 2004;Kulmala et al, 2004) which is favored at lower temperatures.…”
Section: Discussionsupporting
confidence: 93%
“…Diesel school buses and coach passenger buses were identified as strong local sources of UFPs while walking and driving, respectively, and this observation is consistent with previous findings (Abraham et al, 2002;Levy et al, 2003;Westerdahl et al, 2005). Interestingly, UFP exposures on public transit buses in Montre´al were more than twice those reported for diesel school buses in Fredericton, New Brunswick (Health Canada, 2005); suggesting that traffic density likely (expected to be lower in Fredericton than in Montre´al) plays an important role in determining in-vehicle exposures.…”
Section: Discussionsupporting
confidence: 92%
“…Wind speed and direction have a large effect on CO, NO 2 and PM 10 , a pattern also found elsewhere (e.g. Levy et al, 2003). Both precipitation variables have some importance for PM 10 but have little effect on the other three pollutants.…”
supporting
confidence: 54%
“…Finlayson-Pitts and Pitts, 1986;Levy et al, 2003;Aldrin and Haff, 2005;Hussein et al, 2006;Cheng et al, 2007;Prtenjak et al, 2009Prtenjak et al, , 2013Klaić et al, 2012Klaić et al, , 2015. Past investigations focusing on the interplay between meteorology and air quality in Croatia can be grouped as follows: 1) Modelling of the long-range transport of airborne pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, children tend to be more susceptible to UFP toxicity when compared to adults, particularly due to their undeveloped immune and respiratory systems (Schwartz 2004;Foos et al, 2008). Ultrafine particles may originate outdoors, from vehicle emissions and gas-to-particle conversions (Levy et al, 2003;Vigotti et al, 2007). However, indoor UFP originate from a wide range of indoor sources and occupant-related activities such as cooking, smoking, cleaning, and painting (Wallace et al, 2002;Vinzents et al, 2005;Weichenthal et al, 2007).…”
mentioning
confidence: 99%